Unveiling the influence of lateralized carotid artery revascularization on cognitive function: a comparative analysis - Wu, Sensen; Ning, Yachan; Wang, Hui; Guo, Julong; Gao, Xixiang; Wang, Chunmei; Gu, Yongquan; Guo, Lianrui (Frontiers in Neurology, 2025)
ObjectiveTo investigate and compare the changes in cognitive function after carotid artery revascularization surgery on different sides.MethodsFrom April 2019 to April 2021, patients with ≥70% carotid artery stenosis who were treated with carotid endarterectomy (CEA) or carotid artery stenting (CAS) were recruited for this study. The Montreal Cognitive Assessment (MoCA) instrument was used to evaluate cognitive function preoperatively and at 3, 6, and 12 months postoperatively. Patients were divided into two groups based on the side of the surgery, repeated measures ANOVA was used for comparisons.ResultsA total of 89 patients who met the criteria were enrolled and completed 1-year follow-up. At 3, 6, and 12 months after carotid revascularization, the total MoCA score and delayed recall score were significantly improved compared with the baseline scores (p < 0.05). In patients who underwent left-sided revascularization, verbal fluency showed improvement at 12 months compared to baseline levels (p < 0.05). In patients who underwent right-sided revascularization, attention showed improvement at 6 months compared to baseline, and the improvement in delayed recall at 6 and 12 months was still evident compared to the 3-month assessment (p < 0.05).ConclusionCarotid revascularization can improve cognitive function in patients, with differences in cognitive function changes observed between left and right carotid revascularization procedures.